Examining Qatari humanitarian diplomacy: key features, challenges and prospects - Ghassan Elkahlout (17906894) (2024)
In recent years, Qatar has emerged as a key actor in humanitarian diplomacy (HD), which has received limited academic attention. This paper provides an analysis of Qatar’s engagement with HD, drawing on a literature review and extensive interviews with officials and humanitarian workers in Qatar, observations of state activities and humanitarian agencies, and personal interviews with international humanitarian aid workers. The study reveals Qatar’s unique strategy, characterised by its diplomatic stance and the integrated efforts of its governmental and non-governmental sectors, as foundational to its HD efforts. The study also reports challenges hindering those efforts, namely the impacts of the political tensions, the lack of diplomatic immunity for humanitarian workers, and a scarcity of specialised expertise in HD. These are explored in terms of their implications for the effectiveness of Qatar’s efforts, emphasising the critical need for enhanced supportive frameworks, targeted capacity-building initiatives, and well-defined protocols for HD engagement. To add to the dialogue on HD, this paper reflects on Qatar’s engagement in HD, suggesting that smaller nations can meaningfully contribute when leveraging their strengths and international relationships. Other Information Published in: Third World Quarterly License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01436597.2024.2379345